Zasięg i znaczenie zwyczajów we współczesnym handlu międzynarodowym - Kamiński, Zenon (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2007)
It is generally admitted that commercial customs play an important role in international trade of today. The characteristics of commercial customs (usages) can be found as well in international Conventions, as also in generally appreciated rules of trading e.g. the Warsaw-Oxford Rules 1932, or Incoterms 2000. Customs (usages) are widely respected not only in contracts of sale, but also in contracts of carriage and insurance. In spite of the rising role of international commercial law, there is still much room for the role of customs (usages) in international commercial transactions. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2007; nr 1173, s. 175-184